A Case Report of Hypertriglyceridemia-Associated Acute Pancreatitis Following Use of Brazil Nut Weight-Loss Supplement. (December 2022) - Von Ruden, Serena; Slusarenko, Natalie; Webster, Daniel
Purpose: Brazil nuts ( Bertholletia excelsa ) are consumed world-wide and have become a new trend in weight loss supplementation. We present a unique case of severe hypertriglyceridemia-associated acute pancreatitis following daily usage of a Brazil nut supplement product. Summary: A Hispanic female presented with severe hypertriglyceridemia and acute pancreatitis several months after starting a Brazil nut weight loss supplement in the setting of poorly controlled Type 2 Diabetes Mellitus. Her initial triglyceride level was undetectably high >10, 000 mg/dL but improved rapidly following euglycemic insulin infusion and supplement cessation. The patient was managed with supportive care, started on oral fibrate therapy after abdominal symptoms improved, and was discharged to home in stable condition. Conclusion: It is essential for pharmacists to maintain a high index of suspicion for patients taking complementary and alternative medications and supplements who present with acutely altered laboratory parameters or onset of acute disease. In this instance, a patient was found to have profound hypertriglyceridemia with onset of acute pancreatitis following usage of a Brazil nut weight loss supplement.